1996
DOI: 10.1063/1.363755
|View full text |Cite
|
Sign up to set email alerts
|

Strain effect on electronic and optical properties of GaN/AlGaN quantum-well lasers

Abstract: In order to clarify the strain effect on the GaN-based lasers and to give the important guideline on their device design, the subband structure and the optical gains of strained wurtzite GaN/AlGaN quantum wells are theoretically investigated on the basis of k⋅p theory. First-principles band calculations are used for deriving the unknown physical parameters. It is found that neither compressive nor tensile biaxial strains in the c plane are so effective on the reduction of the threshold carrier density as conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
2
8

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 19 publications
2
37
2
8
Order By: Relevance
“…As shown in Fig. 3 the wave number of the E 2 H peak was 566 cm À 1 very similar to the reported data (567 cm À 1 ) [22], which confirmed that the micro-wire was strain-free [23,24]. Also, this Raman data verifies the high quality of the micro-wire, which was grown under near atmospheric pressure.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…As shown in Fig. 3 the wave number of the E 2 H peak was 566 cm À 1 very similar to the reported data (567 cm À 1 ) [22], which confirmed that the micro-wire was strain-free [23,24]. Also, this Raman data verifies the high quality of the micro-wire, which was grown under near atmospheric pressure.…”
Section: Resultssupporting
confidence: 88%
“…In an optical device, for example, an undesired shift of the emission wavelength can be caused by a change in the band structure due to internal stress [22]. Also, dislocations made by biaxial stress can degrade the performance of the device.…”
Section: Resultsmentioning
confidence: 99%
“…We have already studied the electronic and optical properties of WZ GaN/AlGaN QWs, including strain effects, based on the k.p theory [3,4,5,6]. The physical parameters have been derived from the first-principles band calculations [4,5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The physical parameters have been derived from the first-principles band calculations [4,5,7,8]. It was found that the threshold carrier density of WZ nitride LDs is higher than conventional ZB LDs [3,4] and that the biaxial strain is not so effective to reduce it [4,6]. In addition, it was suggested that the uniaxial strain in the c-plane is very useful for reducing it [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation